9(y-4)=3y-6

Simple and best practice solution for 9(y-4)=3y-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9(y-4)=3y-6 equation:


Simplifying
9(y + -4) = 3y + -6

Reorder the terms:
9(-4 + y) = 3y + -6
(-4 * 9 + y * 9) = 3y + -6
(-36 + 9y) = 3y + -6

Reorder the terms:
-36 + 9y = -6 + 3y

Solving
-36 + 9y = -6 + 3y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-3y' to each side of the equation.
-36 + 9y + -3y = -6 + 3y + -3y

Combine like terms: 9y + -3y = 6y
-36 + 6y = -6 + 3y + -3y

Combine like terms: 3y + -3y = 0
-36 + 6y = -6 + 0
-36 + 6y = -6

Add '36' to each side of the equation.
-36 + 36 + 6y = -6 + 36

Combine like terms: -36 + 36 = 0
0 + 6y = -6 + 36
6y = -6 + 36

Combine like terms: -6 + 36 = 30
6y = 30

Divide each side by '6'.
y = 5

Simplifying
y = 5

See similar equations:

| x^3-3x=21 | | (3x^3+10x+5)-(x^3+4x-6)= | | -2x-23=3(x+4) | | 4c^3-8=100 | | -6(U+2)=4u+38 | | -3v+5(v-2)=-20 | | 14=5(x+5)+6x | | 14=4(w-4)-7w | | -c(5)-23=-18 | | x+16=2x+4 | | x+16=2x+3 | | 48+3w+10w=100 | | (8x^2)+(3x^2-2)= | | -3q^2+30q-48=0 | | 3x-90=46 | | 2x+6=2(x-8)+10 | | 4x^2-9y^2-16x-18y=29 | | m+(-13)=(-18) | | 293=3x | | 4/5/17+y=6/16/17 | | x=-3y+17 | | 4y^2+16y+21= | | y=3.5x+6.1 | | -6(3x-6)=120 | | -23=2x+3(-x-4) | | -2=-15-x | | 6z+24=6z+4 | | 6y-4-3y+1= | | 4(2m+1)=36 | | 2/3n+3=9 | | 14+5x=3(-3x+3)-11 | | 7k+5=4k-19 |

Equations solver categories